REFORMULATION STRATEGY OF EDUCATIONAL INSTITUTION IN FACING COMPETITION WITH A BALANCED SCORECARD APPROACH - Joseph M.J Renwarin; Hendy Tannady; Fransiska E. SUharjanti; Alusia A. K. Vavyanti; Anna Y. Purwaningsih (Proceeding of International Conference on Entrepreneurship (IConEnt), 2022)
The number of school-age population in Bekasi City, West Java Province, Indonesia is very large, reaching around 24 percent of the total population in the city. This condition opens up opportunities for the education in-depth interviews, discussions, and questionnaires. The interviews involved students, graduates, and parents from competing schools. Analysis of data evaluation using the balanced scorecard. The recommendation strategy uses the SMART concept. The research results require market penetration, product development, and correction of internal weaknesses by taking advantage of external opportunities. industry to develop educational services that are able to attract students' interest in Bekasi City, West Java. This study aims to recommend the development of strategies that are applied in Senior High School and Vocational Senior High School under the auspices of the XYZ Education Organization. In this study, researchers used Research and Development (R&D) research with a qualitative approach to collect data and explore data through